Manières ethnologues de faire avec de la littérature - Nicolas Adell (Contextes)
This article aims at describing the forms and stakes of the ways in which ethnologists use literary processes or texts, but also the figures of the writer. The author identifies three main ones. Firstly, he gives an account of an anthropology with the writer. Within this realm, the ethnologist follows the author's methods in terms of descriptive strategy or ways of telling some truth. Secondly, he outlines the contours of a literary anthropology that aims, on the one hand, at the overcoming of literary criticism by the analytical resources of ethnology, and, on the other hand, at the implementation of narrative procedures to account for social life. Thirdly, an anthropology of the writer endeavors to mobilize ethnography in order to describe creative processes and their different materializations.